Overt Mycobacterium avium subsp. paratuberculosis Infection: An Infrequent Occurrence in Archived Tissue from False TB Reactor Cattle in Michigan, USA - Scott D. Fitzgerald; Steven R. Bolin; Kathryn G. Boland; Ailam Lim; John B. Kaneene (Veterinary Medicine International)
The objective of this study was to retrospectively determine whether or not cattle from the state of Michigan which were classified as bovine tuberculosis reactors, based on currently approved field and laboratory testing methods, were overtly infected with Mycobacterium avium subsp. paratuberculosis (MAP). Included in this study were 384 adult cattle submitted to the Diagnostic Center for Population and Animal Health over a seven-year period. Cattle were tested utilizing standard methods to confirm that all cattle were lesion and culture negative for infection with Mycobacterium bovis at postmortem examination. Retrospective analysis of formalin-fixed, paraffin-embedded sections of ileum and ileocecal lymph node were evaluated by histopathology, acid-fast staining, and PCR assays to detect MAP. Overall, only 1.04 percent of cattle showed overt infection with MAP on visual examination of sections of ileum and/or ileo-cecal lymph node. This increased slightly to 2.1 percent of cattle likely infected with MAP after additional testing using a PCR assay. Based on these results, we found no evidence that overt infection with MAP plays a major role in the false tuberculosis reactor test results for cattle examined in this study.